Risk factors for unsuppressed viral load after intensive adherence counseling among HIV infected persons in Kampala, Uganda: a nested case–control study - Jonathan Izudi; Barbara Castelnuovo; Rachel King; Adithya Cattamanchi (AIDS Research and Therapy, 2023)
Abstract Background Intensive adherence counseling (IAC) is the global standard of care for people living with human immunodeficiency virus (PLHIV) who have unsuppressed VL after ≥ 6 months of first-line anti-retroviral therapy (ART). We investigated whether the number of IAC sessions is associated with suppressed VL among PLHIV in Kampala, Uganda. Methods We conducted a nested case-control study among PLHIV with unsuppressed VL after ≥ 3 IAC sessions (cases) and a 2:1 random sample of PLHIV with suppressed VL after ≥ 3 IAC sessions (controls). Unsuppressed VL was defined as VL ≥ 1000 copies/ml. We performed multivariable logistic regression to identify factors that differed significantly between cases and controls. Results Demographic and clinical characteristics were similar among the 16 cases and 32 controls including mean age, sex, baseline CD4 count, VL before IAC, and WHO clinical stage. Only the number of IAC sessions differed significantly between cases and controls in unadjusted (p = 0.012) and adjusted (p = 0.016) analyses. Each unit increase in IAC session was associated with unsuppressed VL (Adjusted odds ratio 5.09; 95% CI 1.35–19.10). Conclusions VL remained unsuppressed despite increasing IAC frequency. The fidelity to standardized IAC protocol besides drug resistance testing among PLHIV with unsuppressed VL before IAC commencement should be examined.